A Kirigami-Engineered “Skeletal Framework” Composite for Ultralow Hysteresis and Highly Stable Strain Sensors - Pongampai, Satana; Chaithaweep, Kanokwan; Pakawanit, Phakkhananan; Charoonsuk, Thitirat; Bongkarn, Theerachai; Maluangnont, Tosapol; Vittayakorn, Wanwilai; Hajra, Sugato; Kim, Hoe Joon; Vittayakorn, Naratip (My University, 2025)
Wearable strain sensors are pivotal for next-generation human–machine interfaces, yet achieving high fidelity, robustness, and sustainability in a single platform remains a significant challenge. A primary obstacle is the inherent viscoelasticity of soft materials, which leads to signal drift and hysteresis. Here, we report a highly stretchable and ultrastable strain sensor fabricated through a synergistic integration of Kirigami-based structural engineering and nanocomposite material design. By introducing titanium dioxide nanotubes (TNTs) into a bacterial cellulose (BC) matrix, we create a composite with a unique internal “skeletal framework”. This framework substantially reduces viscoelastic losses, resulting in an exceptionally low hysteresis of 0.6% and ensuring robust performance with 99.4% signal stability over >10 000 cycles. Concurrently, the Kirigami-patterned structure enhances stretchability to ∼235% while the framework amplifies sensitivity 5.8-fold. The practical viability of this high-fidelity sensor is demonstrated through the precise and repeatable control of a robotic arm, where ultralow hysteresis proves more critical than raw sensitivity. The sensor’s eco-friendly, water-based fabrication aligns high-fidelity sensing with sustainable processing, presenting a clear design paradigm for engineering reliable and eco-conscious wearable electronic devices.
Keywords: Bacterial cellulose; Robotic arm control; Stability; Strain sensor; Stretchability